POLA KEMITRAAN PARIWISATA DALAM MANAJEMEN ATRAKSI DESA WISATA PAMPANG KOTA SAMARINDA - , Ami Suswandi Putra ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Pampang Tourism Village or Desa Wisata Pampang is the only culturebased tourism in Samarinda. Thatâs why it became a valuable asset which should be fully supported in management system, but did not show significant progress after 20 years. This research aimed to identify the partnerships characteristics of attraction management in Pampang Tourism Village, and formulate improvements that should be implemented. The method used was grounded research with a qualitative approach. The main data is activities of various actors obtained by interview and observation. Those activities are then classified based on similar properties, so the existing partnership patterns can be identified and a thorough evaluation can be conducted. Various problems found were revisited to determine the improved formulation, adapted to the theories. The entire research process successively performed with domain analysis, taxonomy analysis, componensial analysis, themes analysis, and triangulation analysis. The results showed that the existing partnership model belonging to the pseudo partnership and subordinate union of partnership. The existing partnership is dominated by the relief fund patterns, including Grant in Aid for physical improvements and PNPM Mandiri in Tourism, Private Investment, CSR, Revolving Loan Fund (KUD), Sub Contracts and General Trade. Management of the existing tourist attraction gave insufficient space on human resources development, created gap between tourism activities and social cultural life of community, limited use of technology and provided a small number of community organization. Therefore improvement plan should be designed on boosting of Private Investment, establishing participation for reformer agents and academics, expanding community involvement on Pelas Tahun Ceremony, granting savings and loans, and generating KUD as the core of social tourism activities.